Durable photocatalytic self-cleaning fluoride-free waterproof material as well as preparation method and application thereof

By loading cationized titanium dioxide nanoparticles on the fiber surface and hydrolyzing and condensing with the silicon oxygen group in the modified polyurethane emulsion, the problem of existing waterproof materials being difficult to remove and damage to fibers when facing oily stains is achieved, and fabrics are realized The superhydrophobic and photocatalytic surface self-cleaning effect improves the friction resistance and water washing stability of the waterproof material.

CN119392505AActive Publication Date: 2025-02-07SICHUAN TEXTILE SCI RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411835188.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-07
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing waterproof materials are difficult to remove when facing oily stains, and the photocatalytic effect will damage the fiber surface, resulting in reduced waterproofing performance and poor friction and washing resistance.

Method used

By loading cationized titanium dioxide nanoparticles with photocatalytic effects on the surface of the fibers, and hydrolyzing and condensing the silicon oxygen group in the modified polyurethane emulsion with the hydroxyl group of the cationized titanium dioxide nanoparticles, a stable chemical bond is formed, giving the fabric good waterproofing Durability, and the low surface energy substances are migrated to the outer layer by heat treatment, restoring hydrophobic properties.

Benefits of technology

It realizes the dual-function self-cleaning effect of superhydrophobic and photocatalytic fabric surface, improves the friction resistance and water washing stability of the waterproof material, and extends the durability of the waterproof performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a durable photocatalytic self-cleaning fluoride-free waterproof material as well as a preparation method and application thereof, and relates to the technical field of waterproof materials, the durable photocatalytic self-cleaning fluoride-free waterproof material comprises the following components in parts by mass: 0.2-3 parts of cationized titanium dioxide nanoparticles and 30-90 parts of modified polyurethane emulsion. According to the preparation method, TiO2 nanoparticles with a photocatalytic effect are loaded on the fiber surface, low-surface-energy substances in the inner layer are migrated to the outermost layer by adopting a heat treatment method, the hydrophobic property of the fabric surface is repaired by utilizing the physical characteristics of titanium dioxide, the hydrophobic durability of the fabric surface is further improved, and the hydrophobic property of the fabric surface is improved. The waterproof material is endowed with a lasting and excellent waterproof effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof materials, and in particular to a durable photocatalytic self-cleaning fluorine-free waterproof material and a preparation method and application thereof. Background Art

[0002] Organic-inorganic nanohybrid is a new composite material system that combines organic and inorganic components at the nanoscale. Through the synergistic effect of each component at the micro-nanoscale, it can present unique properties different from those of a single component. Inspired by the micro-nanoscale rough structure of lotus leaves, scientists have constructed organic components with low surface energy and inorganic rough structures at the micro-nanoscale on the surface of fabrics, making the contact angle of water droplets on the fabric surface exceed 150° and extremely easy to roll off. This type of fabric surface can resist the pollution of water-based stains and has self-cleaning ability. It is widely used in fabric waterproof finishing. However, once the surface of waterproof fabric is stained with oily stains, it is difficult to remove the oil stains simply by rolling water droplets, and the adhesion of oil stains will cause the waterproof performance to weaken. Loading nanoparticles with photocatalytic effect on the fiber surface can achieve photodegradation of organic pollutants adhering to the fabric surface.

[0003] At present, most methods for achieving self-cleaning of waterproof surfaces are mainly achieved by the anti-wetting property of the self-cleaning surface to aqueous droplets, but do not show obvious anti-fouling performance to some common organic pollutants in life. After adding photocatalytic nanoparticles to the self-cleaning coating, the degradation of organic pollutants can be achieved by simple illumination. Depending on whether the low surface energy material used contains fluorine, the self-cleaning photocatalytic coating can be roughly divided into two categories: fluorine-free self-cleaning photocatalytic waterproof fabrics and fluorine-containing self-cleaning photocatalytic waterproof fabrics.

[0004] Good waterproof performance can be achieved on the fabric surface by using fluorine-free low surface energy materials. Compared with fluorine-containing coatings, this type of coating has the advantage of being green and environmentally friendly, but its disadvantage is that it is not resistant to chemical corrosion and has poor waterproof durability. In addition, most coatings use organic solvents to prepare the coatings, and water-based coatings that do not contain organic solvents comply with environmental protection requirements and are one of the important directions for future development in this field.

[0005] Since fluorine-containing substances have lower surface energy and compared with fluorine-free hydrophobic carbon long chains, this type of compound has a stable chemical structure and is more difficult to be destroyed by photocatalysts during the photocatalytic process, so it can achieve more stable and lasting hydrophobic properties. However, the inherent defect of fluorine-containing compounds that they are difficult to degrade has greatly limited the application market of self-cleaning fabrics.

[0006] In addition, while the photocatalytic effect decomposes organic pollutants, it also damages the low surface energy substances coated on the fiber surface, thereby causing a gradual decrease in waterproof performance, which in turn leads to poor friction and water washing resistance of the self-cleaning coating. Therefore, the present invention will start from solving the above problems and intends to construct a super hydrophobic and photocatalytic dual-function self-cleaning coating on the surface of the fabric, and make the coating have self-healing ability against photocatalytic damage and high friction and water washing stability, so as to realize the preparation of long-term self-cleaning fabrics. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a durable photocatalytic self-cleaning fluorine-free waterproof material and a preparation method and application thereof.

[0008] The objective of the present invention is achieved through the following technical solutions: A durable photocatalytic self-cleaning fluorine-free waterproof material comprises 0.2 to 3 parts by mass of cationized titanium dioxide nanoparticles and 30 to 90 parts by mass of modified polyurethane emulsion.

[0009] The cationic titanium dioxide nanoparticles include, by mass, 1 to 6 parts of tetrabutyl titanate, 1 to 6 parts of long-chain alkyltrimethoxysilane, 0.5 to 3 parts of ammonia water, 35 to 65 parts of ethanol, 0.5 to 1.5 parts of γ-(methacryloyloxy)propyltrimethoxysilane, 0.05 to 0.15 parts of acetic acid, 0.005 to 0.01 parts of an initiator, and 70 to 130 parts of water.

[0010] The long-chain alkyltrimethoxysilane is one of dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane.

[0011] The modified polyurethane emulsion comprises, by weight, 6 to 18 parts of polytetrahydrofuran, 10 to 50 parts of terminal hydroxyl polysiloxane, 12 to 19 parts of N-methyldiethanolamine, 0.005 to 0.1 parts of an organic bismuth compound Coscat® 83AC83 catalyst, 12 to 38 parts of isophorone diisocyanate, 10 to 20 parts of glycerol carbonate, 1 to 10 parts of aminopropyltrialkoxysilane, 6 to 14.2 parts of glacial acetic acid, and 50 to 160 parts of water.

[0012] The polytetrahydrofuran is one of PTMG600, PTMG800, PTMG1000, PTMG2000, PTMG2500, PTMG3000, PTMG3500 and PTMG4000, the aminopropyltrialkoxysilane is aminopropyltriethoxysilane, and the terminal hydroxyl polysiloxane is one of PDMS1000, PDMS1500, PDMS2000, PDMS3000, PDMS3600 and PDMS4500.

[0013] The second aspect of the present invention provides a method for preparing a durable photocatalytic self-cleaning fluorine-free waterproof material, comprising the following steps: adding cationic titanium dioxide nanoparticles to a modified polyurethane emulsion, and reacting at 25 to 45° C. with stirring for 3 to 5 hours.

[0014] The preparation of cationic titanium dioxide nanoparticles comprises the following steps: S1: Tetrabutyl titanate, long-chain alkyl trimethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, ammonia water and ethanol are mixed, stirred and reacted at 30-60° C. for 8-16 hours, and hydrophobically modified and double-bond modified titanium dioxide nanoparticles are synthesized by centrifugation, precipitation and washing; S2: The prepared titanium dioxide nanoparticles, acetic acid, initiator, dimethylaminoethyl methacrylate and water are mixed and dispersed by ultrasonication, and the mixture is kept at 60-85° C. for 3-5 hours to obtain cationic titanium dioxide nanoparticles.

[0015] The preparation of the modified polyurethane emulsion comprises the following steps: mixing polytetrahydrofuran, isophorone diisocyanate, N-methyldiethanolamine and an organic bismuth compound Coscat® 83 AC83 catalyst, heating to 65-90°C, keeping stirring and reacting for 1-4 hours; adding glycerol carbonate after the reaction, keeping warm at 30-60°C and reacting for 1-4 hours; adding aminopropyltrialkoxysilane after the reaction, keeping warm at 30-60°C and reacting for 1-4 hours; after the reaction, adding glacial acetic acid in an amount equal to the mole of N-methyldiethanolamine and reacting for 1-4 hours; after the reaction system cools to room temperature, adding glacial acetic acid in an amount equal to the mole of N-methyldiethanolamine and carrying out a neutralization reaction to obtain a polyurethane prepolymer, adding water to the prepolymer for mechanical emulsification to obtain a modified polyurethane emulsion.

[0016] The third aspect of the present invention provides an application of a durable photocatalytic self-cleaning fluorine-free waterproof material in waterproof finishing of pure cotton, polyester-cotton, polyester and other fabrics.

[0017] The beneficial effects of the present invention are: (1) Based on the dual-functional hydrolysis condensation reaction and free radical thermal polymerization grafting theory, the present invention uses dimethylaminoethyl methacrylate to graft the titanium dioxide nanoparticles modified with γ-(methacryloyloxy)propyltrimethoxysilane double bonds and long carbon chains to perform surface cationization, thereby achieving stable dispersion of titanium dioxide nanoparticles in water and avoiding the problem of emulsifier residues in traditional emulsion polymerization products, avoiding the generation of harmful waste liquid, and making the PvAC product purer; (2) The present invention hydrolyzes and condenses the siloxy groups in the modified polyurethane emulsion with the hydroxyl groups in the surface cationized modified titanium dioxide nanoparticles and selectively deblocks the isocyanate groups by the ester organic compounds at different application temperatures, so that the exposed isocyanate groups react with the hydroxyl groups on the surface of the substrate, thereby achieving stable chemical bonding between the organic and inorganic components in the waterproofing agent and between the waterproofing agent and the fabric, thereby giving the finished fabric good waterproof durability; (3) In view of the inherent defects of existing waterproofing additives that can only resist water-based stains after being used for fabric surface finishing, while oily stains are difficult to remove and the adhesion of oily stains will cause the waterproof performance to weaken and thus affect the waterproof durability, the present invention loads TiO2 nanoparticles with photocatalytic effect on the fiber surface, uses a heat treatment method to make the low surface energy substances in the inner layer migrate to the outermost layer, and uses the physical properties of titanium dioxide itself to repair the hydrophobic properties of the fabric surface, thereby promoting further improvement of the hydrophobic durability of the fabric surface, and giving the waterproof material a long-lasting and excellent waterproof effect. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0019] The ammonia water used in this embodiment is commercially available industrial ammonia water. Example

[0020] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 4 g of tetrabutyl titanate, 2 g of long-chain alkyl trimethoxysilane, 1 g of γ-(methacryloyloxy)propyl trimethoxysilane, 2 g of ammonia water (28% mass fraction), 50 g of water and 50 g of ethanol and add them to a reaction bottle in sequence, mix them, heat them to 60°C at a speed of 300 rpm, keep them warm for 8 hours, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.1 g acetic acid, 0.01 g AIBN (dispersant), 1 g dimethylaminoethyl methacrylate, and 50 g water were ultrasonically dispersed in a reaction bottle, kept at 80° C. for 3 h, and centrifugally dried to obtain cationic titanium dioxide nanoparticles.

[0021] Preparation of modified polyurethane emulsion: S1: 6g of polytetrahydrofuran, 12g of isophorone diisocyanate, 20g of terminal hydroxyl polysiloxane (PDMS1000), and 8g of N-methyldiethanolamine were added to a reaction bottle, and 0.01g of Coscat® 83 AC83 catalyst of an organic bismuth compound was added, and the temperature was raised to 85°C at a speed of 150 rpm for 2 h of heat preservation. The polytetrahydrofuran used in this embodiment is PTMG600; S2: Add 10 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 40°C, and react for 2 h; S3: Add 3 g of aminopropyltrialkoxysilane to the reaction bottle, maintain the reaction temperature at 40°C, and react for 2 hours; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine for neutralization reaction for 30 min, and add 100 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0022] Durable photocatalytic self-cleaning fluorine-free waterproof material: 0.8 g of cationic titanium dioxide nanoparticles was added to 70 g of modified polyurethane emulsion, and the reaction was carried out at 300 rpm and 40°C for 4 hours. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles. Example

[0023] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 4g of tetrabutyl titanate, 3g of long-chain alkyl trimethoxysilane, 1g of γ-(methacryloyloxy)propyl trimethoxysilane, 2g of ammonia water (28% mass fraction), 50g of water and 50g of ethanol and add them into a reaction bottle in sequence, mix them and heat them to 60°C at a speed of 300rpm, keep the temperature for reaction for 8h, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.1 g acetic acid, 0.01 g AIBN (dispersant), 1 g dimethylaminoethyl methacrylate, and 60 g water were ultrasonically dispersed in a reaction bottle, and the mixture was kept at 80° C. for 3 h. Cationic titanium dioxide nanoparticles were obtained by centrifugal drying.

[0024] Preparation of modified polyurethane emulsion: S1: 6g of polytetrahydrofuran, 12g of isophorone diisocyanate, 20g of terminal hydroxyl polysiloxane (PDMS1500), and 8g of N-methyldiethanolamine were added to a reaction bottle, and 0.01g of Coscat® 83 AC83 catalyst of an organic bismuth compound was added, and the temperature was raised to 85°C at a speed of 150 rpm for 2 h of heat preservation. The polytetrahydrofuran used in this embodiment is PTMG800; S2: Add 10 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 40°C, and react for 2 h; S3: Add 3 g of aminopropyltrialkoxysilane to the reaction bottle, maintain the reaction temperature at 40°C, and react for 2 hours; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine for neutralization reaction for 30 min, and add 100 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0025] Durable photocatalytic self-cleaning fluorine-free waterproof material: 0.5 g of cationic titanium dioxide nanoparticles was added to 70 g of modified polyurethane emulsion, and the reaction was carried out at 300 rpm and 40°C for 4 hours. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles. Example

[0026] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 1g of tetrabutyl titanate, 1g of long-chain alkyl trimethoxysilane, 0.5g of γ-(methacryloyloxy)propyl trimethoxysilane, 0.5g of ammonia water (28% mass fraction), 35g of water and 35g of ethanol and add them into a reaction bottle in sequence, mix them and heat them to 60°C at a speed of 300rpm, keep the temperature for reaction for 8h, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.05 g acetic acid, 0.05 g AIBN (dispersant), 0.5 g dimethylaminoethyl methacrylate, and 35 g water were ultrasonically dispersed in a reaction bottle, kept at 80° C. for 3 h, and the cationic titanium dioxide nanoparticles were obtained by centrifugal drying.

[0027] Preparation of modified polyurethane emulsion: S1: 10g of polytetrahydrofuran, 14g of isophorone diisocyanate, 10g of terminal hydroxyl polysiloxane (PDM2000), and 10g of N-methyldiethanolamine were added to a reaction bottle, and 0.005g of organic bismuth compound Coscat® 83 AC83 catalyst was added, and the temperature was raised to 85°C at a speed of 150 rpm for 2 h. The polytetrahydrofuran used in this embodiment is PTMG1000; S2: Add 10 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 40°C, and react for 2 h; S3: Add 5 g of aminopropyltrialkoxysilane to the reaction bottle, maintain the reaction temperature at 40°C, and react for 2 hours; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine and react for 30 minutes, then add 50 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0028] Durable photocatalytic self-cleaning fluorine-free waterproof material: 2 g of cationic titanium dioxide nanoparticles were added to 90 g of modified polyurethane emulsion and reacted at 300 rpm and 40°C for 4 h. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles. Example

[0029] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 2g of tetrabutyl titanate, 2g of long-chain alkyl trimethoxysilane, 0.5g of γ-(methacryloyloxy)propyl trimethoxysilane, 1g of ammonia water (28% mass fraction), 50g of water and 50g of ethanol and add them into a reaction bottle in sequence, mix them, heat them to 60°C at a speed of 300rpm, keep them warm for 8h, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.1 g acetic acid, 0.005 g AIBN (dispersant), 1 g dimethylaminoethyl methacrylate, and 50 g water were ultrasonically dispersed in a reaction bottle, kept at 80° C. for 3 h, and centrifugally dried to obtain cationic titanium dioxide nanoparticles.

[0030] Preparation of modified polyurethane emulsion: S1: 8g of polytetrahydrofuran, 18g of isophorone diisocyanate, 20g of terminal hydroxyl polysiloxane (PDMS3000), and 12g of N-methyldiethanolamine were added to a reaction bottle, and 0.01g of Coscat® 83 AC83 catalyst of an organic bismuth compound was added, and the temperature was raised to 85°C at a speed of 150 rpm for 2 h of heat preservation. The polytetrahydrofuran used in this embodiment is PTMG2000; S2: Add 15 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 40°C, and react for 2 h; S3: Add 8 g of aminopropyltrialkoxysilane to the reaction bottle, maintain the reaction temperature at 40°C, and react for 2 hours; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine and react for 30 min, then add 80 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0031] Durable photocatalytic self-cleaning fluorine-free waterproof material: 0.8 g of cationic titanium dioxide nanoparticles was added to 50 g of modified polyurethane emulsion, and the reaction was carried out at 300 rpm and 40°C for 4 hours. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles. Example

[0032] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 3g of tetrabutyl titanate, 4g of long-chain alkyl trimethoxysilane, 1.5g of γ-(methacryloyloxy)propyl trimethoxysilane, 2g of ammonia water (28% mass fraction), 60g of water and 60g of ethanol and add them into a reaction bottle in sequence, mix them and heat them to 30°C at a speed of 300rpm, keep the temperature for reaction for 16h, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.15 g acetic acid, 0.015 g AIBN (dispersant), 1.5 g dimethylaminoethyl methacrylate, and 60 g water were ultrasonically dispersed in a reaction bottle, kept at 60° C. for 5 h, and the cationic titanium dioxide nanoparticles were obtained by centrifugal drying.

[0033] Preparation of modified polyurethane emulsion: S1: 11g of polytetrahydrofuran, 20g of isophorone diisocyanate, 30g of terminal hydroxyl polysiloxane (PDMS3600), and 12g of N-methyldiethanolamine were added to a reaction bottle, and 0.01g of Coscat® 83 AC83 catalyst of an organic bismuth compound was added, and the temperature was raised to 85°C at a speed of 150 rpm for 2 h of heat preservation. The polytetrahydrofuran used in this embodiment is PTMG2500; S2: Add 18 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 50°C, and react for 2 h; S3: Add 10 g of aminopropyltrialkoxysilane to the reaction bottle, maintain the reaction temperature at 40°C, and react for 2 hours; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine for neutralization reaction for 30 min, and add 100 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0034] Durable photocatalytic self-cleaning fluorine-free waterproof material: 3 g of cationic titanium dioxide nanoparticles were added to 90 g of modified polyurethane emulsion and reacted at 300 rpm and 40°C for 4 h. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles. Example

[0035] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 5g of tetrabutyl titanate, 6g of long-chain alkyl trimethoxysilane, 1.5g of γ-(methacryloyloxy)propyl trimethoxysilane, 3g of ammonia water (28% mass fraction), 60g of water and 60g of ethanol and add them into a reaction bottle in sequence, mix them and heat them to 50°C at a speed of 200rpm, keep the temperature for reaction for 10h, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.1 g acetic acid, 0.01 g AIBN (dispersant), 0.5 g dimethylaminoethyl methacrylate, and 65 g water were ultrasonically dispersed in a reaction bottle, kept at 85° C. for 4 h, and centrifugally dried to obtain cationic titanium dioxide nanoparticles.

[0036] Preparation of modified polyurethane emulsion: S1: 10g of polytetrahydrofuran, 30g of isophorone diisocyanate, 40g of terminal hydroxyl polysiloxane (PDMS4500), and 15g of N-methyldiethanolamine were added to a reaction bottle, and 0.01g of Coscat® 83 AC83 catalyst of an organic bismuth compound was added, and the temperature was raised to 65°C at a speed of 50 rpm for 4 hours. The polytetrahydrofuran used in this embodiment is PTMG4000; S2: Add 20 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 30°C, and react for 4 hours; S3: Add 1 g of aminopropyltrialkoxysilane to the reaction flask, maintain the reaction temperature at 60°C, and react for 1 hour; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine and react for 30 min, then add 150 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0037] Durable photocatalytic self-cleaning fluorine-free waterproof material: 0.8 g of cationic titanium dioxide nanoparticles was added to 70 g of modified polyurethane emulsion, and the reaction was carried out at 45°C at a rotation speed of 200 rpm for 3 hours. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles. Example

[0038] Preparation of cationic titanium dioxide nanoparticles: S1: Weigh 6 g of tetrabutyl titanate, 6 g of long-chain alkyl trimethoxysilane, 1.5 g of γ-(methacryloyloxy)propyl trimethoxysilane, 3 g of ammonia water (28% mass fraction), 65 g of water and 65 g of ethanol and add them to a reaction bottle in sequence, mix them, heat them to 30°C at a speed of 400 rpm, keep them warm for 8 hours, centrifuge, precipitate and wash to obtain hydrophobically modified and double-bond modified titanium dioxide nanoparticles; S2: The prepared nanoparticles, 0.15 g acetic acid, 0.01 g AIBN (dispersant), 1.5 g dimethylaminoethyl methacrylate, and 65 g water were ultrasonically dispersed in a reaction bottle, kept at 60° C. for 5 h, and centrifugally dried to obtain cationic titanium dioxide nanoparticles.

[0039] Preparation of modified polyurethane emulsion: S1: 16g of polytetrahydrofuran, 38g of isophorone diisocyanate, 50g of terminal hydroxyl polysiloxane (PDMS1000), and 19g of N-methyldiethanolamine were added to a reaction bottle, and 0.01g of Coscat® 83 AC83 catalyst of an organic bismuth compound was added, and the temperature was raised to 85°C at a speed of 150 rpm for 2 h of heat preservation. The polytetrahydrofuran used in this embodiment is PTMG1000; S2: Add 20 g of glycerol carbonate into the reaction flask, maintain the reaction temperature at 60 °C, and react for 1 h; S3: Add 3 g of aminopropyltrialkoxysilane to the reaction bottle, maintain the reaction temperature at 30°C, and react for 4 hours; S4: After the temperature of the reaction system drops to room temperature, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine and react for 30 min, then add 160 g of water for mechanical emulsification to obtain a polyurethane emulsion.

[0040] Durable photocatalytic self-cleaning fluorine-free waterproof material: 0.2 g of cationic titanium dioxide nanoparticles was added to 30 g of modified polyurethane emulsion, and the reaction was carried out at 25°C at a rotation speed of 200 rpm for 3 hours. A durable photocatalytic self-cleaning fluorine-free waterproof material was obtained through the hydrolysis condensation of the siloxy groups in the modified polyurethane emulsion and the hydroxyl groups in the surface cationic modified titanium dioxide nanoparticles.

[0041] Comparative Example 1 Different from Example 1, the titanium dioxide particles in the comparative example are not cationized. The specific preparation method of the titanium dioxide particles is as follows: S1: According to the mass fraction, weigh 4g of tetrabutyl titanate, 2g of long-chain alkyltrimethoxysilane, 1g of γ-(methacryloyloxy)propyltrimethoxysilane, 2g of ammonia water (28% mass fraction), 50g of water and 50g of ethanol mixed solution, add them into the deionized water in the reaction bottle in sequence, mix them, heat them to 60°C at a speed of 300rpm, keep them warm for 8h, then centrifuge, precipitate and wash to obtain long carbon chain modified titanium dioxide nanoparticles.

[0042] Comparative Example 2 Different from Example 1, glycerol carbonate is not added for modification when preparing the modified polyurethane emulsion.

[0043] Comparative Example 3 Different from Example 1, aminopropyltrialkoxysilane is not added for modification when preparing the modified polyurethane emulsion.

[0044] Comparative Example 4 test: The waterproof material prepared in the examples and comparative examples was used to treat cotton fabrics with 80 g / L of water repellent using a padding and baking finishing process. After the fabrics were impregnated, the liquid was squeezed out at a residual rate of 70% and baked at 110°C for 2 min. In addition, a group of waterproof materials prepared in Example 1 was used to treat cotton fabrics with 80 g / L of water repellent using a padding and baking finishing process. After the fabrics were impregnated, the liquid was squeezed out at a residual rate of 70% and baked at 150°C for 2 min as comparative example 4.

[0045] Analysis of fabric surface and waterproof effect: Compared with Comparative Example 1, the emulsion state of all embodiments is more stable, and the surface of the fabric after finishing has better waterproof durability. The prepared emulsion according to the formula of each embodiment is finished on the surface of the fabric and washed 30 times. Similarly, the emulsion prepared by the formula of Comparative Example 1 is finished on the surface of the fabric using the same method and washed 30 times. Different liquids (milk, water droplets, coffee, tea, soy milk) are dropped on the surface of the fabric after finishing and washing. The experiment found that: the liquid on the surface of the fabric finished and washed by the formula of each embodiment presents a relatively regular spherical shape, showing good The comparative example 1 has a hydrophobic effect, and when different liquids (milk, water, coffee, tea, soy milk) are dropped on the surface of the washed and finished fabric in comparative example 1, the liquid presents an irregular elliptical shape. This is because the titanium dioxide nanoparticles in the embodiment are surface cationized and show better water dispersibility. After being finished on the fabric surface, stable chemical bonds are formed between the organic and inorganic components in the waterproofing agent, and between the waterproofing agent and the fabric. In comparative example 1, the titanium dioxide nanoparticles have too few surface hydroxyl groups and are only physically adhered to the fabric surface, so the waterproof durability effect is poor.

[0046] Compared with Comparative Example 2, all the embodiments showed poor waterproof durability after being finished on the fabric surface. The emulsion prepared by the formula of Comparative Example 2 was finished on the fabric surface using the same method and washed 30 times. Different liquids (milk, water drops, coffee, tea, soy milk) were dropped on the surface of the finished and washed fabric and compared with each embodiment. The experiment found that when different liquids (milk, water drops, coffee, tea, soy milk) were dropped on the surface of the finished fabric after washing in Comparative Example 2, the liquids showed irregular elliptical shapes, and the waterproof effect was significantly worse than the hydrophobic effect of the fabric surface finished and washed using the formulas of each embodiment. This is because no glycerol carbonate was added in Comparative Example 2, so that the waterproofing agent did not form a chemical bond with the fabric surface, and thus showed poor waterproof durability.

[0047] Similarly, using the same method, all embodiments are compared with Comparative Example 3. Comparative Example 3 shows poor waterproof effect after the fabric surface is washed 30 times. That is, Comparative Example 3 shows poor waterproof durability. This is because aminopropyltriethoxysilane is not added to Comparative Example 3, so that the inorganic components in the waterproofing agent lack chemical bonds with the organic components, and thus the waterproof durability is worse.

[0048] Compared with Comparative Example 4, Example 1 shows similar photocatalytic self-cleaning effect and waterproof durability after being finished on the fabric surface even at different treatment temperatures. This is because glycerol carbonate can form stable chemical bonds with the fabric surface even at lower setting temperatures, showing excellent waterproof durability.

[0049] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A durable photocatalytic self-cleaning fluorine-free waterproof material, characterized by: The invention comprises 0.2 to 3 parts of cationic titanium dioxide nanoparticles and 30 to 90 parts of modified polyurethane emulsion by weight.

2. The fluorine-free waterproof material according to claim 1, characterized in that: The cationic titanium dioxide nanoparticles include, by mass, 1 to 6 parts of tetrabutyl titanate, 1 to 6 parts of long-chain alkyltrimethoxysilane, 0.5 to 3 parts of ammonia water, 35 to 65 parts of ethanol, 0.5 to 1.5 parts of γ-(methacryloyloxy)propyltrimethoxysilane, 0.05 to 0.15 parts of acetic acid, 0.005 to 0.01 parts of an initiator, and 70 to 130 parts of water.

3. The fluorine-free waterproof material according to claim 2, characterized in that: The long-chain alkyltrimethoxysilane is one of dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane.

4. The fluorine-free waterproof material according to claim 1, characterized in that: The modified polyurethane emulsion comprises, by weight, 6 to 18 parts of polytetrahydrofuran, 10 to 50 parts of terminal hydroxyl polysiloxane, 12 to 19 parts of N-methyldiethanolamine, 0.005 to 0.1 parts of an organic bismuth compound Coscat® 83 AC83 catalyst, 12 to 38 parts of isophorone diisocyanate, 10 to 20 parts of glycerol carbonate, 1 to 10 parts of aminopropyltrialkoxysilane, 6 to 14.2 parts of glacial acetic acid, and 50 to 160 parts of water.

5. The fluorine-free waterproof material according to claim 4, characterized in that: The polytetrahydrofuran is one of PTMG600, PTMG800, PTMG1000, PTMG2000, PTMG2500, PTMG3000, PTMG3500 and PTMG4000, the aminopropyltrialkoxysilane is aminopropyltriethoxysilane, and the terminal hydroxyl polysiloxane is one of PDMS1000, PDMS1500, PDMS2000, PDMS3000, PDMS3600 and PDMS4500.

6. The method for preparing a durable photocatalytic self-cleaning fluorine-free waterproof material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: adding cationic titanium dioxide nanoparticles into modified polyurethane emulsion, and reacting at 25-45° C. with stirring for 3-5 hours.

7. The method according to claim 6, characterized in that: The preparation of the cationic titanium dioxide nanoparticles comprises the following steps: S1: Tetrabutyl titanate, long-chain alkyl trimethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, ammonia water and ethanol are mixed, stirred and reacted at 30-60° C. for 8-16 hours, and hydrophobically modified and double-bond modified titanium dioxide nanoparticles are synthesized by centrifugation, precipitation and washing; S2: The prepared titanium dioxide nanoparticles, acetic acid, initiator, dimethylaminoethyl methacrylate and water are mixed and dispersed by ultrasonication, and the mixture is kept at 60-85° C. for 3-5 hours to obtain cationic titanium dioxide nanoparticles.

8. The preparation method according to claim 6, characterized in that: The preparation of the modified polyurethane emulsion comprises the following steps: Mix polytetrahydrofuran, isophorone diisocyanate, N-methyldiethanolamine and organic bismuth compound Coscat® 83AC83 catalyst, heat to 65-90°C, keep stirring and react for 1-4 hours; add glycerol carbonate after the reaction, keep warm at 30-60°C for 1-4 hours; add aminopropyltrialkoxysilane after the reaction, keep warm at 30-60°C for 1-4 hours; after the reaction, add glacial acetic acid in an amount equal to that of N-methyldiethanolamine to neutralize the reaction, and obtain a polyurethane prepolymer; add water to the prepolymer for mechanical emulsification to obtain a modified polyurethane emulsion.

9. Use of the durable photocatalytic self-cleaning fluorine-free waterproof material according to any one of claims 1 to 5 in waterproof finishing of pure cotton, polyester-cotton, polyester and other fabrics.

Citation Information

Patent Citations

  • Super-hydrophobic fabric coating with dual functions of UV photodegradation and NIR photo-thermal responsive self-repairing and preparation method of super-hydrophobic fabric coating

    CN115717338A

  • Self-repairing and self-cleaning super-hydrophobic protective coating and preparation method thereof

    CN115874441A